Evaluasi Kinerja Pengawasan Pendidikan Agama Islam Di Kabupaten Temanggung. - Herny Juniasri (MSI 14 UMY 033, 2014)
This study aims to determine, analyze and evaluate: 1) planning; 2) preparation; 3) method, media and evaluation; and 4) the work performance results of Islamic Education Supervisor at Temanggung Regency based on Islamic education teacher’s. This research applies a qualitative descriptive approach with CIPP evaluation method including Contex, Input, Process and Product. The collecting data method is done with questionnaires, interviews, observation and documentation. It can be concluded in this thesis that the overall work performance of Islamic education teacher supervisors at Temanggung Regency has not contributed with maximal to the Islamic education teacher supervision , because supervisors are still fixated with the task of correcting, and they have not searched for a solution and dual role of supervisors as academic supervisor and managerial supervisor. Likewise, the supervisors still need education and training, especially in the field of research and development.